Do a Visual Presentation - Stacey Ellison (EDIS, 2015)
A visual presentation, either a demonstration or an illustrated talk, is a teaching method in which the presenter shares information with an audience with the assistance of visual aids such as posters, models, and computer presentation software. This 4-page fact sheet covers the method of delivery, the plan, the visuals, how to look sharp and to have a sharp presentation. Written by Stacey Ellison, and published by the UF Department of 4-H Youth Development, June 2015.